Identifying Andesite Rocks Sources Using Geoelectrical Resistivity in Loli, Donggala Regency, Central Sulawesi - Harsano Jayadi; Icha Untari Meidji; Basyri Yadi Tang (JPSE (Journal of Physical Science and Engineering), 2019)
Research has been carried out in Loli Village, Donggala Regency, Central Sulawesi using the Wenner-Schlumberger resistivity geoelectric method to determine the resource of andesite rocks. This measurement was done by determining the path points in the field using the Global Positioning System (GPS). The data collection was carried out using the geoelectrical resistivity method based on the area’s measurement plan. The data obtained was in the form of position data for each electrode, potential data (V), and current strength data (I) used to calculate the resistivity value (r). The results obtained from this research are andesite rock resource content, which was characterized by a high resistivity value ranging from 300–600 Wm. The resistivity value of the cover layer is low, ranging from 14–45 Wm. The latent content of andesite rocks was dominated in the southeast region on the trajectory of DRSA_01, DRSA_02, DRSA_03, DRSA_04, and DRSA_06 which had a lower topography than the northwest region. DOI: http://dx.doi.org/10.17977/um024v4i22019p045